2017
DOI: 10.1016/j.jsp.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of retention in elementary grades on dropping out of school early

Abstract: This study investigated the effect of grade retention in elementary school on dropping out of school by age 16. Participants were 538 (54% males) ethnically diverse, academically at-risk students recruited from Texas schools into a longitudinal study when they were in first grade (mean age = 6.58). Propensity score weighting successfully equated the 171 retained students and the 367 continuously promoted students on 65 covariates assessed in grade 1. Fifty-one students dropped out of school by age 16 and 487 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 67 publications
(85 reference statements)
1
26
0
4
Order By: Relevance
“…On the other hand, many researchers have found adverse effects of grade retention on socioemotional development, social adjustment, and academic performance. Numerous studies have reported that grade retention not only does not improve students' performance, but has a negative impact on one's self-esteem, academic self-concept, social and emotional adjustment, attitudes towards school, and increases school dropout rates (Alexander et al, 2001;Holmes & Matthews, 1984;Hughes et al, 2017;Jimerson, 2001). In other words, there is no guarantee that having students ST012Q09NA Musical instruments (e.g.…”
Section: Schsize Envawarementioning
confidence: 99%
“…On the other hand, many researchers have found adverse effects of grade retention on socioemotional development, social adjustment, and academic performance. Numerous studies have reported that grade retention not only does not improve students' performance, but has a negative impact on one's self-esteem, academic self-concept, social and emotional adjustment, attitudes towards school, and increases school dropout rates (Alexander et al, 2001;Holmes & Matthews, 1984;Hughes et al, 2017;Jimerson, 2001). In other words, there is no guarantee that having students ST012Q09NA Musical instruments (e.g.…”
Section: Schsize Envawarementioning
confidence: 99%
“…Partiendo de investigaciones previas, en niveles socioeconómicos bajos, se puede asegurar que la repetición, inicialmente puede conducir una mejora en el rendimiento (Magnuson et al, 2004), posteriormente puede conllevar repercusiones negativas a corto, mediano y largo plazo (González-Betancor & López-Puig, 2016). A corto plazo, existe mayor probabilidad de abandono educativo entre los escolares repetidores que entre los que son promocionados de manera continua (Hughes et al, 2017). A medio plazo, podrían existir mejoras en la atención de los escolares, pero no en los resultados académicos (Mantzicopoulos & Morrison, 1992).…”
Section: Introductionunclassified
“…Sin embargo, no se ha encontrado la misma relación entre repetición en educación primaria y la probabilidad de abandono, de manera que haber repetido en esta etapa no tendría un peso significativo en el futuro abandono escolar. Estos resultados contradicen la afirmación de que repetir en educación primaria aumentaría la probabilidad de abandono escolar temprano, especialmente entre los estudiantes en riesgo por causas personales y sociofamiliares (Hughes, Cao, West, Smith y Cerda, 2017;Stearns, Moller, Blau, Potochnick, 2007). En consecuencia, nuestros hallazgos apuntan a que la repetición en primaria no parece ser relevante para la intención de abandono.…”
Section: Discussionunclassified